Microbiological quality of marketed ricotta cheese and disease risks associated with Listeria monocytogenes contamination - Esper, Luciana Maria Ramires (2011)
The present study aimed at evaluating the quality of ricotta cheeses marketed in the region of Campinas, SP, and to characterize the pathogenic potential of the isolated Listeria monocytogenes strains. Of 45 analyzed samples, 46.7% (21/45) did not comply with the Brazilian microbiological standard established. Most of the evaluated samples showed the microorganisms counts above those established by the regulation, that is, 46.7% for thermotolerant coliforms, 2.2% for coagulase-positive staphylococci, and 6.7% for Listeria monocytogenes. No Salmonella was isolated from these samples. It was evidenced the ocurrence of Listeria monocytogenes strains, with virulence genes acta type 4 and hly type 1, and classified as lineage I, which indicate the pathogenic potential for human. This study evidenced that this class of product deserves more attention from the scientific community, and also from manufacturing sector and sanitary surveillance bureau, improving the products quality, and consequently the consumer safety.